PERTANGGUNG JAWABAN PENGEMUDI DALAM HAL TERJADINYA KECELAKAAN MENURUT PASAL 359 DAN PASAL 360 KUHP - JUNUS JUNUS; ANA INDRAWATI; LUCIUS ANDIK RAHMANTO (Institut agama islam negeri Padangsidimpuan, 2022)
This study aims to examine how 359 and 360 of the Criminal Code apply to drivers who cause someone to die in a traffic accident. This search is a regular search with descriptive search results. The method used in this search is the legal process for an emerging court, and the data required includes the first data and the second data. The quality assessment system is a systematic review system designed to provide a clear picture of the application of articles 359 and 360 of the Criminal Code in cases of motor vehicle accidents. From the results of the investigation and discussion, it can be concluded that in the case of an accident that causes the death of the victim, legal experts use Articles 359 and 360 of the Criminal Code. The note on negligence applies to the application of the provisions of the criminal law against the negligence of the driver causing the accident. Article 359 of the Criminal Code,